Desain Sistem Navigasi Robot Berkaki Enam pada Model Lahan Tanaman Padi - Khairul Anam (Pusat Penelitian Informatika - LIPI, 2011)
This article presents a robot design used in agriculture field for controlling rat pest in paddy fields. The robot is hexapod type with single actuator in every leg. It has two kind of controller, low-level controller and high level controller. The low-level controller guarantees the leg rotation in 360 degrees. The high-level controller is behavior-based controller with a coordinator. The performance of each behavior was tested as well as the overall system. This research yielded a robot that could operate in grassy and muddy environment and it could move with speed 3.9 cm/s.